Efektivitas Metode Cooperatif Learning dan Jig Saw Learning Terhadap Belajar Siswa - Savitaria Savitaria (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2019)
Learning outcomes are the culmination of all teaching and learning activities, because they are part of the benchmarks for the assessment of learners and teachers through various learning patterns and methods within a certain period of time. This is to become a new and further framework for teaching and learning activities (KBM). Learning outcomes are also inspired by methods from the teacher to students and their feedback. Various types of learning methods have been used as a learning formulation, one of which is Jig Saw Learning, this method is an interesting strategy to use if the material to be studied can be divided into several parts and the material is not in the order. The advantages of this strategy are all students learn and teach others. This method is can be implemented in various subjects with supporting capacities and tools such as syllabus, implementation of learning (RPP), student activity sheets (LKS), formative tests, and test validity. In this study the authors conducted a study to what extent the effectiveness of the Jig Saw Learning method was applied in Indonesian language lesson by comparing the theory with the application of the method, not only on learning outcomes, but also on students' understanding and mastery of the subject matter.